Síndrome de Burnout y Satisfacción Laboral del personal de enfermería en el marco de la pandemia COVID -19 - Choque Mallma, Miryan Veronica (2023)
The research aimed to determine the relationship between the Burnout Syndrome level and job satisfaction in the framework of the COVID-19 pandemic of the nursing staff of the Neonatology service of the Hipólito Unanue Tacna Hospital in 2020. Methodology: Descriptive study, cross-sectional and correlational design. The sample consisted of 28 nursing professionals. Two instruments were used, the Maslach Burnout questionnaire and the Font Roja questionnaire to measure the job satisfaction of nurses. Results: In relation to the Burnout syndrome variable, it was found that 89.30% had a medium level of Burnout Syndrome and 10.71% a low level of Burnout Syndrome. Regarding the job satisfaction variable, it was found that 82.10% have a medium level of job satisfaction and 17.90% have a low level of job satisfaction in nursing staff. The relationship of both variables when performing the Chi Square statistical test was obtained with a value of p=0.019 < α = 0.05 with which it was concluded that there is a relationship between burnout syndrome and job satisfaction in nursing staff. Conclusion: There is a relationship between burnout syndrome and job satisfaction in nursing staff.